PERJALANAN PENCARIAN DIRI TOKOH RAIB DALAM NOVEL BUMI KARYA TERE LIYE (Kajian Psikologi Sastra) - Wilda Wijayanti; Andi Karman; Aslan Abidin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the self-identity search of Raib, the main character in Bumi by Tere Liye, using a literary psychology approach. This research employs a qualitative descriptive method. The data consist of narrative and dialogue excerpts from the novel that reflect inner conflict, identity crisis, and psychological development of the character. Data were collected through close reading and note-taking techniques, while data analysis was conducted through identification, classification, and interpretation based on concepts of literary psychology. The results indicate that Raib’s self-identity search occurs gradually, beginning with identity confusion and inner conflict, followed by self-acceptance, and culminating in the formation of an integrated identity. This process is influenced by personal experiences, internal and external conflicts, as well as moral values that shape the character’s psychological development. This study is expected to contribute to Indonesian literary studies, particularly research on novels using a literary psychology perspective.